Heat of the Lava Dragon - West, Tracey, 1965-; Howells, Graham (New York : Branches/Scholastic Inc., 2021)
Drake's friends Mina and Caspar, their dragons, and Worm were trapped in stone by the evil wizard Astrid who has stolen their dragons' powers, but Drake himself was saved from a similar fate by Astrid's sister Hulda; now because of his strong connection with Worm, Drake is able to help his dragon to break free, but to free the others they need the assistance of three other dragons--a lava dragon, a sea dragon, and a wind dragon--and they have to do it before Astrid can steal the powers of even more dragons.
600L
Decoding demand: 75 (high) Semantic demand: 93 (very high) Syntactic demand: 73 (high) Structure demand: 84 (very high)
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Rescues -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Fantasy fiction; Action and adventure fiction